2022
DOI: 10.1038/s41419-022-05502-4
|View full text |Cite
|
Sign up to set email alerts
|

AKAP8L enhances the stemness and chemoresistance of gastric cancer cells by stabilizing SCD1 mRNA

Abstract: Gastric cancer (GC) remains the third leading cause of cancer-related deaths. Chemoresistance is the major determinant of GC treatment failure. To explore the molecular mechanisms of GC chemoresistance, mass spectrometry was performed to detect the genes altered in expression between chemoresistant and chemosensitive GC. PRKA kinase anchor protein 8L (AKAP-8L) was identified as one of the top upregulated genes in chemoresistant GC tissues. Moreover, the higher AKAP-8L expression was associated with the lower s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As demonstrated by studies, AKAP8L stimulates cell proliferation / migration in various cancers, such a sd colon cancer, gastric cancer and esophageal squamous cell carcinoma, and can interact with mTORC1 and promote cell growth. Thus, it may be a prospective target for the treatment of cancers [ 9 , 15 , 16 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by studies, AKAP8L stimulates cell proliferation / migration in various cancers, such a sd colon cancer, gastric cancer and esophageal squamous cell carcinoma, and can interact with mTORC1 and promote cell growth. Thus, it may be a prospective target for the treatment of cancers [ 9 , 15 , 16 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously proved that the high AKAP8L expression is associated with poor prognosis in esophageal squamous cell carcinoma, serving as an independent prognostic factor for the disease [ 9 ]. Zhang et al found that AKAP8L can enhance the dryness and chemoresistance of gastric cancer cells by stabilizing the expression of SCD1 mRNA [ 15 ]. A previous study proved that AKAP8L can promote cell growth by interacting with mTORC1 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…IGF2BPs not only promote cancer progression but also blunt the sensitivity to anti-tumor therapies. In a nutshell, IGF2BPs expedite the development of drug resistance by enhancing tumor stemness 5 , 116 , blocking apoptosis 19 , inducing metabolic reprogramming 16 , 64 , 70 , etc. Logically, it follows that targeting IGF2BPs may be a novel anti-tumor strategy.…”
Section: Targeting Igf2bps As Potential Therapeutic Biomarkers In Tumorsmentioning
confidence: 99%
“…Luo et al showed that SCD1 expression supported radiation resistance in esophageal squamous cell carcinoma [ 164 ]. Zhang et al showed that SCD1 was essential to stem cell-like behavior and chemoresistance in gastric carcinoma [ 165 ]. Morais et al [ 166 ] and Parik et al [ 167 ] showed that glioblastoma aggressiveness and temozolomide resistance depended on SCD1 expression.…”
Section: Detailed Description Of the Steps In The Lmrs Hypothesismentioning
confidence: 99%